Separator for electrochemical device, electrochemical device including the separator, and method for preparing the separator

By using binder resin and inorganic particles in the separator of lithium secondary batteries, and improving the crystallinity and tensile strength of the separator through a stretching process, the problems of shrinkage and dimensional change of the separator at high temperatures are solved, and the battery's performance is improved. Safety and workability.

CN114503352BActive Publication Date: 2025-01-21LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080067181.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-18
Filing Date
2020-10-16
Publication Date
2025-01-21
Estimated Expiration
2040-10-16

AI Technical Summary

Technical Problem

The porous polymer diaphragms of existing lithium secondary batteries will shrink or melt at high temperatures, resulting in low heat resistance. At the same time, the size changes in the self-standing diaphragms may occur during use, increase in interface resistance between the electrode and the diaphragm, and lithium deposition. The problem.

Method used

By using a combination of binder resin and inorganic particles in the separator, the crystallinity of the binder resin is increased, and the tensile strength and dimensional stability of the separator are improved through the stretching process.

Benefits of technology

The high tensile strength and small dimensional changes of the separator are achieved, which improves the safety and processability of the battery and avoids the problems of thermal shrinkage and increased resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114503352B_ABST
    Figure CN114503352B_ABST
Patent Text Reader

Abstract

The separator of the present invention mainly comprises inorganic particles and a binder resin, can be used as a self-supporting separator without a separator substrate (e.g., a polymer resin film), and does not cause a heat shrinkage problem. In addition, in the separator of the present invention, since the crystallinity of the binder resin is increased by stretching, the tensile strength is increased, and a smaller dimensional change is caused after impregnation with an electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the priority of Korean Patent Application No. 10-2019-0130072 filed in Korea on October 18, 2019. The present disclosure relates to a separator for an electrochemical device and an electrochemical device including the separator. The present disclosure also relates to a method for manufacturing a separator. Background Art

[0002] Recently, in the field of electrochemical devices, the guarantee of safety has received more and more attention. In particular, secondary batteries, such as lithium secondary batteries, include an electrode assembly including a positive electrode, a negative electrode and a separator, and the electrode assembly can be manufactured so that it can have a structure in which the separator is placed between the positive electrode and the negative electrode. A porous film using a polyolefin polymer resin has been used as a separator substrate for such a lithium secondary battery. However, such a porous polymer film shrinks or melts at high temperatures, resulting in a problem of low heat resistance. In order to solve this problem, a porous polymer film coated with an inorganic particle coating on the surface, or a self-supporting separator containing only an inorganic material and a binder resin without a polymer separator substrate has been proposed. When an inorganic material is applied to a separator as described above, thermal shrinkage and safety can be improved. However, the resulting separator may experience an increase in thickness and dimensional changes in width and length due to its volume expansion, resulting in a defect in the appearance of the battery. In addition, the separation of the separator from the electrode will generate bubbles in the battery, the interface resistance between the electrode and the separator increases, and lithium may be deposited in the gap between the electrode and the separator, resulting in a problem of increased battery resistance. Therefore, it is necessary to reduce the dimensional variation of the self-supporting separator. In addition, when such a self-supporting separator is used to manufacture a battery, it is necessary to increase the tensile strength of the separator to ensure processability during battery assembly. Summary of the invention

[0003] Technical issues

[0004] The present disclosure is intended to solve the problems of the related art, and therefore the present disclosure is intended to provide a self-supporting diaphragm including a binder resin and inorganic particles. In particular, the present disclosure relates to providing a diaphragm having improved tensile strength due to the improved crystallinity of the binder resin by stretching, and having a small dimensional change after being impregnated with an electrolyte. The present disclosure is also intended to provide a method for manufacturing a diaphragm having the above-mentioned structural features. In addition, the present disclosure is intended to provide an electrochemical device comprising a positive electrode, a negative electrode, a diaphragm disposed between the positive electrode and the negative electrode, and an electrolyte, wherein the diaphragm is the above-mentioned diaphragm. These and other objects and advantages of the present disclosure can be understood from the following detailed description and will become more apparent from the exemplary embodiments of the present disclosure. In addition, it is easily understood that the objects and advantages of the present disclosure can be achieved by the means and combinations thereof shown in the appended claims.

[0005] Technical Solution

[0006] According to a first embodiment of the present disclosure, a diaphragm including an insulating porous layer is provided, wherein the insulating porous layer contains inorganic particles and a binder resin, and the inorganic particles are present in an amount of 70 wt % to 90 wt % based on 100 wt % of the insulating porous layer; based on 100 wt % of the binder resin, the binder resin contains more than 50 wt % of a polyvinylidene fluoride homopolymer, and the crystallinity of the binder resin is more than 50%.

[0007] According to a second embodiment of the present disclosure, there is provided a separator as defined in the first embodiment, wherein inorganic particles in the insulating porous layer are bound to each other by a binder resin, and the insulating porous layer has a porous property of pores derived from interstitial volumes between the inorganic particles.

[0008] According to a third embodiment of the present disclosure, there is provided a separator as defined in the first or second embodiment, wherein the inorganic particles include a 2 O 3 、AlOOH、Al(OH) 3 、AlN、BN、MgO、Mg(OH) 2 、SiO 2 , ZnO, TiO 2 and BaTiO 3 At least one of the groups consisting of.

[0009] According to a fourth embodiment of the present disclosure, there is provided a separator as defined in any one of the first to third embodiments, wherein an average particle diameter of the inorganic particles is 0.001 μm to 3 μm.

[0010] According to a fifth embodiment of the present disclosure, there is provided a separator as defined in any one of the first to fourth embodiments, wherein the molecular weight (Mw) of the polyvinylidene fluoride homopolymer is 600,000 g / mol to 2,000,000 g / mol.

[0011] According to a sixth embodiment of the present disclosure, there is provided a separator as defined in any one of the first to fifth embodiments, the separator including only one or more insulating porous layers.

[0012] According to a seventh embodiment of the present disclosure, there is provided a method of manufacturing the separator defined in any one of the first to sixth embodiments, the method including the step of stretching the insulating porous layer in at least one direction.

[0013] According to an eighth embodiment of the present disclosure, there is provided a method as defined in the seventh embodiment, wherein the insulating porous layer has a rectangular planar shape with an aspect ratio greater than 1, and the method includes the step of stretching the insulating porous layer in the transverse and / or longitudinal directions.

[0014] According to a ninth embodiment of the present disclosure, there is provided a method as defined in the seventh or eighth embodiment, wherein the step of stretching the insulating porous layer is performed under heating.

[0015] According to a tenth embodiment of the present disclosure, there is provided the method as defined in the ninth embodiment, wherein the step of stretching the insulating porous layer is performed within a temperature range from a glass transition temperature of the binder resin to a melting point of the binder resin.

[0016] Beneficial effects

[0017] The separator of the present disclosure basically comprises inorganic particles and a binder resin, can be used as a self-supporting separator that does not include a separator substrate (e.g., a polymer resin film), and does not cause thermal shrinkage problems. In addition, the separator of the embodiment of the present disclosure has increased tensile strength due to improved crystallinity of the binder resin by stretching, and shows less dimensional change after impregnation with an electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings illustrate preferred embodiments of the present disclosure and, together with the foregoing disclosure, are used to provide a further understanding of the technical features of the present disclosure. Therefore, the present disclosure is not interpreted as being limited to the accompanying drawings.

[0019] Figure 1 is a schematic diagram showing a step of stretching an insulating porous layer according to an embodiment of the present disclosure.

[0020] Figure 2 is a schematic diagram showing an insulating porous layer stretched in two directions perpendicular to each other. DETAILED DESCRIPTION

[0021] Hereinafter, the preferred embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. Before the description, it should be understood that the terms used in the specification and the appended claims should not be interpreted as limited to the general and dictionary meanings, but are interpreted based on the meanings and concepts corresponding to the technical aspects of the present disclosure based on the principle of allowing the inventor to appropriately define the terms to obtain the best interpretation. Therefore, the description presented herein is only a preferred embodiment for illustrative purposes and is not intended to limit the scope of the present invention, so it should be understood that other equivalent substitutions and modifications may be made thereto without departing from the scope of the present disclosure.

[0022] The terms used in the specification are for illustrative purposes only and are intended to describe exemplary embodiments, but the scope of the present disclosure is not limited thereto. As used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0023] In addition, it should be understood that when used in this specification, the terms "including", "having" or "comprising" refer to the existence of any specified shapes, numbers, steps, operations, parts, elements and / or groups, but do not exclude the addition of one or more other shapes, numbers, steps, operations, parts, elements and / or their groups.

[0024] In one aspect of the present disclosure, an insulating porous layer is provided. The insulating porous layer can be used as a separator of an electrochemical device. In this article, a typical example of an electrochemical device may be a rechargeable secondary battery including a unit cell formed by stacking a positive electrode, a separator, and a negative electrode in sequence.

[0025] In another aspect of the present disclosure, a diaphragm for an electrochemical device comprising the insulating porous layer is provided, in particular a self-supporting diaphragm comprising only the insulating porous layer. According to the present disclosure, the self-supporting diaphragm is a diaphragm comprising only the insulating porous layer and not including any other elements (e.g., a diaphragm substrate, such as a polymer resin film) other than the insulating porous layer of the present disclosure.

[0026] According to one embodiment of the present disclosure, the insulating porous layer is an organic / inorganic composite film including inorganic particles and a binder resin. In the insulating porous layer, the inorganic particles are bound to each other by the binder resin so that they can be stacked in a layered structure. According to the present disclosure, the organic / inorganic composite film has a porous characteristic of pores formed by the interstitial volume between the inorganic particles. The interstitial volume refers to the space defined by the inorganic particles that are substantially facing each other in the stacking structure of the inorganic particles. The pores are interconnected so that a gas or liquid can pass from one surface of the substrate through the substrate to the other surface thereof.

[0027] According to an embodiment of the present disclosure, there is no particular limitation on the inorganic particles, as long as they are electrochemically stable and have a particle size that is compatible with the thickness of the insulating porous layer. In other words, there is no particular limitation on the inorganic particles used according to the present disclosure, as long as they are within the operating voltage range of the applicable battery (e.g., based on Li / Li + The inorganic particles may have a particle size of 0.001-3 μm or 0.001-2 μm. When the size of the inorganic particles is less than 0.001 μm, the dispersibility may be reduced. When the size of the inorganic particles is greater than 3 μm, it is difficult to provide the resulting insulating porous layer in the form of a film. Therefore, when the insulating porous layer is applied alone to the diaphragm, the diaphragm exhibits an excessively large pore size, resulting in deterioration of the insulating properties. In view of the above, the inorganic particles may be controlled to have a particle size of about 20-500 nm.

[0028] Non-limiting examples of inorganic particles include Al 2 O 3 、AlOOH、Al(OH)3 、AlN、BN、MgO、Mg(OH) 2 、SiO 2 , ZnO, TiO 2 、BaTiO 3 or a mixture thereof.

[0029] In addition, there is no particular limitation on the binder resin as long as it provides binding force for the inorganic particles and imparts binding force between the insulating porous layer and the electrode. Based on 100% by weight of the insulating porous layer, the insulating porous layer may include 70-90% by weight of inorganic particles. When the content of the inorganic particles is too high, the content of the binder resin is reduced, so the inorganic particles may be easily detached from the insulating porous layer, and the insulating porous layer may exhibit low durability, including brittleness. On the contrary, when the content of the inorganic particles is too low, the proportion of the binder resin increases and the insulating porous layer shows low porosity, resulting in deterioration of the resistance characteristics.

[0030] The thickness of the insulating porous layer is not particular. For example, the insulating porous layer may have a thickness of 0.01 to 50 μm.

[0031] In addition, the insulating porous layer is not particularly limited in terms of its pore size and porosity. Preferably, the insulating porous layer may have a pore size of 0.001-3 μm or 0.001-2 μm and a porosity of 10-90% by volume. The pore size and porosity depend largely on the size of the inorganic particles, but may be affected by the type of binder resin. For example, when inorganic particles with a particle size of 1 μm or less are used, the pore size may be about 1 μm or less. This pore structure is filled with an electrolyte subsequently injected, and the electrolyte acts as a conductive ion. When the pore size and porosity are less than 0.001 μm and less than 10% by volume, respectively, the resulting insulating porous layer may act as a resistive layer. When the pore size and porosity are greater than 10 μm and greater than 90% by volume, respectively, the resulting insulating porous layer may exhibit reduced mechanical properties.

[0032] In addition, the method for measuring porosity and pore size is not particularly limited, and the micropore volume and mesopore volume can be measured by the Brunauer-Emmett-Teller method using an adsorbed gas (e.g., nitrogen), or by using a conventionally used mercury (Hg) intrusion method. In addition, the porosity can be calculated based on the apparent density of the insulating porous layer and the true density of the components forming the insulating porous layer.

[0033] According to an embodiment of the present disclosure, the insulating porous layer may be obtained by preparing a composition for forming an insulating porous layer including inorganic particles and a binder resin, and forming the composition into a sheet-shaped film.

[0034] First, the composition for forming the insulating porous layer can be obtained as follows: a polymer solution containing a binder resin dissolved in a solvent and a dispersion containing inorganic particles dispersed in the solvent are prepared separately, and the polymer solution is mixed with the dispersion. The inorganic particles can be added after being crushed to a predetermined average particle size. Alternatively, the inorganic particles are added to a solvent and then dispersed in the solvent, while being controlled to have a predetermined particle size using a ball milling process, etc., to provide a dispersion. At the same time, according to an embodiment of the present disclosure, the content of solids other than the solvent in the polymer solution can be controlled to be less than 10% by weight, for example, 5-7% by weight. When the solid content is greater than 10% by weight, the binder resin may not be fully dissolved in the solvent. Therefore, it is preferred to control the solid content to be less than 10% by weight. In addition, it is preferred to control the content of solids other than the solvent in the dispersion to be 30-70% by weight.

[0035] The polymer solution and the dispersion can be mixed using a mixing device such as a homodiper. For example, when a homodiper is used to prepare the composition, mixing can be performed at about 2000 rpm for about 30 minutes.

[0036] Then, the composition is applied to the release sheet and dried to form an insulating porous layer. The composition can be applied by a coating method appropriately selected from known coating methods, including dip coating, slit coating, micro gravure coating, line coating and blade coating. In particular, slit coating or dip coating is preferably used. The slit coating method includes applying the composition supplied by the slit die to the entire surface of the release sheet, and the thickness of the applied composition can be controlled according to the flux supplied by the metering pump. In addition, dip coating includes immersing the release sheet in a tank containing the composition for coating, and the thickness of the applied composition can be controlled according to the concentration of the composition and the speed of removing the release sheet from the composition tank.

[0037] Meanwhile, the release sheet is not particularly limited as long as the resulting insulating porous layer is not damaged when it is removed. For example, the release sheet may include a glass plate or a polymer film made of polyethylene terephthalate.

[0038] The solvent for the composition preferably has a solubility parameter and a low boiling point similar to the solubility of the binder resin to be used, so as to promote the removal of the organic solvent during the drying process. This is because such a solvent is conducive to uniform mixing and subsequent removal. In view of the above, the solvent preferably has a boiling point of 80-180°C or 100-165°C. Non-limiting examples of solvents include acetone, tetrahydrofuran, dichloromethane, chloroform, dimethylformamide, N-methyl-2-pyrrolidone (NMP), cyclohexane, mesitylene, dimethylacetamide, dimethyl sulfone, dimethyl carbonate, methyl ethyl ketone, methyl acetate, cyclohexanone, etc. The above solvents can be used alone or in combination. Preferably, the solvent may include any one selected from N-methyl-2-pyrrolidone (NMP), cyclohexane, mesitylene, dimethylacetamide, dimethyl sulfone and dimethyl carbonate or a mixture of two or more thereof.

[0039] According to the present disclosure, the binder resin for the insulating porous layer may include any one selected from the group consisting of polyvinylidene fluoride (PVdF)-based resin, styrene-butadiene rubber (SBR), polytetrafluoroethylene (PTFE), polyethylene glycol (PEG), polypropylene glycol (PPG), toluene diisocyanate (TDI), polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, poly(ethylene-co-vinyl acetate), polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer and polyimide, or a mixture of two or more thereof.

[0040] Specific examples of the polyvinylidene fluoride based binder resin may include any one selected from the group consisting of polyvinylidene fluoride homopolymer, poly(vinylidene fluoride-co-hexafluoropropylene), poly(vinylidene fluoride-co-trichloroethylene), poly(vinylidene fluoride-co-tetrafluoroethylene), poly(vinylidene fluoride-co-trifluoroethylene), poly(vinylidene fluoride-co-chlorotrifluoroethylene) and poly(vinylidene fluoride-co-ethylene), or a mixture of two or more thereof.

[0041] According to the present disclosure, the binder resin may include a polyvinylidene fluoride (PVdF)-based polymer, preferably a polyvinylidene fluoride (PVdF) homopolymer containing vinylidene fluoride as a monomer. According to an embodiment of the present disclosure, based on 100% by weight of the binder resin, the binder resin contains a polyvinylidene fluoride (PVdF) homopolymer in an amount of 50% by weight or more, preferably 75% by weight or more, and more preferably 90% by weight or more.

[0042] Meanwhile, polyvinylidene fluoride (PVdF) homopolymer preferably has a molecular weight (Mw) of 600,000 g / mol to 2,000,000 g / mol. When the molecular weight is less than the above-mentioned limited range, the diaphragm including only the insulating porous layer shows low mechanical strength and degraded durability. On the other hand, when the molecular weight is excessively greater than the above-mentioned limited range, the binder resin exhibits low solubility and degraded processability during the preparation of the polymer solution. For example, the molecular weight can be measured using gel permeation chromatography (GPC), such as PL GPC220 provided by Agilent Technologies.

[0043] Then, the coated composition is dried to remove the solvent and obtain a sheet-like insulating porous layer. The composition can be dried naturally or heated. Heating can generally be carried out by heating processes such as heaters, ovens, resistance heating, electric induction heating, hot air heating, infrared heating, etc. The release sheet can be used not only as a carrier on which the slurry is coated, but also as a component for drying the slurry and removing the organic solvent. Therefore, after providing a heating device for the release sheet, heating can also be carried out by heating the release sheet. The heating can be carried out at a temperature of about 40°C-200°C, preferably about 60°C-180°C. In addition, the heating time is not particularly limited and can be about 10 minutes to 2 hours. After the composition is completely dried, the release sheet is removed to obtain the insulating porous layer.

[0044] Thereafter, the obtained member for an insulating porous layer is stretched to form an insulating porous layer. The stretching may be performed in any one or more specific directions.

[0045] Stretching can be performed using means capable of applying a physical force by which the insulating porous layer can be stretched in a desired direction, and is not limited to any specific method. Figure 1 is a schematic diagram showing the steps of stretching the insulating porous layer of an embodiment of the present disclosure. Here, the insulating porous layer 20 is made to stand upright in the longitudinal direction (direction of gravity), its top is fixed with a first clamp 11, and a weight (second clamp) is hung at its bottom, so that the insulating porous layer can be stretched in the longitudinal direction (direction of gravity). For example, the stretching can be performed in an oven 13 under heating, and the first clamp can be connected to the top of the oven. In a variation, the insulating porous layer can be laid in a direction perpendicular to the direction of gravity (horizontal direction), the first clamp and the second clamp are respectively connected to one end and the other end of the insulating layer, and then the insulating layer can be stretched by stretching it in opposite directions.

[0046] According to one embodiment of the present disclosure, the insulating porous layer may be stretched in a first direction and a second direction, wherein the first direction and the second direction may be perpendicular to each other. For example, when the insulating porous layer has a rectangular planar shape with a width-to-length ratio greater than 1, it may be stretched in the transverse direction and / or the longitudinal direction. When stretching is performed in at least two directions, the stretching in each direction may be performed sequentially or simultaneously. Figure 2 30A and 30B are schematic diagrams showing the insulating porous layer 20 stretched in a first direction 30A and a second direction 30B, wherein the first direction and the second direction are perpendicular to each other.

[0047] Through the stretching step, the binder has an increased degree of orientation and crystallinity. Therefore, the insulating porous layer has improved physical strength and shows little dimensional change even after being immersed in an electrolyte.

[0048] According to an embodiment of the present disclosure, the adhesive preferably exhibits a crystallinity of 50% or more, as determined by the crystallinity band gap intensity of an infrared absorption spectrum. As used herein, crystallinity refers to the weight fraction of the crystalline portion based on the entire polymer resin. The crystallinity can be determined by the following methods: a method assuming that two density values ​​of the crystalline portion and the non-crystalline portion increase / decrease (density method, clean needle technique), a method for determining the crystallinity by fusion heat, a method for determining the crystallinity by dividing the intensity distribution in X-ray diffraction into diffraction originating from the non-crystalline portion and diffraction originating from the crystalline portion (X-ray method), a method for determining the crystallinity by the crystallinity band gap intensity of an infrared absorption spectrum, and the like. In particular, a method for determining the crystallinity by the crystallinity band gap intensity of an infrared absorption spectrum can be used.

[0049] Meanwhile, according to the present disclosure, stretching is preferably performed at an elongation of 10% or less. As used herein, elongation refers to a length increase rate (%) based on an initial length.

[0050] Meanwhile, stretching may be performed while heating the insulating porous layer. According to an embodiment of the present disclosure, stretching is preferably performed within a temperature range from the glass transition temperature of the binder resin to the melting point of the binder resin. When stretching is performed at a temperature below the glass transition temperature, the insulating porous layer cannot be elongated. When stretching is performed at a temperature above the melting point, the binder resin may melt, and the insulating porous layer may break during stretching.

[0051] The insulating porous layer of the present disclosure can be directly used as a separator of an electrochemical device (a free-standing separator). In one variation, the insulating porous layer can be laminated with another separator material having different properties to provide a separator.

[0052] In another aspect, a secondary battery including the separator of the present disclosure is provided. The secondary battery includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, wherein the separator may be composed of the above-mentioned insulating porous layer of the embodiment of the present disclosure. In a variation, the separator may be a composite separator including the insulating porous layer.

[0053] Electrochemical devices include any device that performs an electrochemical reaction, and specific examples thereof include all types of primary batteries, secondary batteries, fuel cells, solar cells or capacitors, such as supercapacitor devices. In particular, among secondary batteries, lithium secondary batteries are preferred, including lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries or lithium ion polymer batteries.

[0054] According to the present disclosure, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on at least one surface of the current collector and containing a positive electrode active material, a conductive material and a binder resin. The positive electrode active material may include any one selected from the following: a layered compound, such as a lithium manganese composite oxide (LiMn 2 O 4 、LiMnO 2 etc.), lithium cobalt oxide (LiCoO 2 ) and lithium nickel oxide (LiNiO 2 ), or those compounds substituted by one or more transition metals; lithium manganese oxides, such as those of the formula Li 1+x Mn 2-x O 4 (where x is 0-0.33), LiMnO 3 、LiMn 2 O 3 and LiMnO 2 Those represented by; lithium copper oxide (Li 2 CuO 2 ); Vanadium oxides, such as LiV 3 O 8 , LiV 3 O 4 、V 2 O 5 Cu 2 V 2 O 7 ; With chemical formula LiNi 1-x M x O 2 Ni-type lithium nickel oxide represented by the chemical formula LiMn 1-x M x O 2(where M = Co, Ni, Fe, Cr, Zn or Ta, x = 0.01 - 0.1) or Li 2 Mn 3 MO 8 The lithium manganese composite oxide represented by (where M = Fe, Co, Ni, Cu or zinc); LiMn in which Li is partially replaced by alkaline earth metal ions 2 O 4 ; a disulfide compound; and Fe 2 (MoO 4 ) 3 ; or a mixture of two or more of them.

[0055] According to the present disclosure, the negative electrode includes a negative electrode current collector and a negative electrode active material layer formed on at least one surface of the current collector and containing a negative electrode active material, a conductive material, and a binder resin. The negative electrode may include any one selected from the following as the negative electrode active material: a lithium metal oxide; carbon, such as non-graphitized carbon or graphitic carbon; a metal composite oxide, such as Li x Fe 2 O 3 (0 ≤ x ≤ 1), Li x WO 2 (0 ≤ x ≤ 1), Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Group 1, 2 or 3 in the periodic table, halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8); lithium metal; a lithium alloy; a silicon-based alloy; a tin-based alloy; metal oxides, such as SnO, SnO 2 , PbO, PbO 2 , Pb 2 O 3 , Pb 3 O 4 , Sb 2 O 3 , Sb 2 O 4 , Sb 2 O 5 , GeO, GeO 2 , Bi 2 O 3 , Bi 2 O 4 and Bi 2 O 5 ; a conductive polymer, such as polyacetylene; a Li - Co - Ni type material; and titanium oxide; or a mixture of two or more of them.

[0056] According to one embodiment of the present disclosure, the conductive material may be any one selected from the group consisting of graphite, carbon black, carbon fiber or metal fiber, metal powder, conductive whisker, conductive metal oxide, activated carbon and polyphenylene derivatives, or a mixture of two or more such conductive materials. More specifically, the conductive material may be any one selected from the group consisting of natural graphite, artificial graphite, Super-P, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate and titanium dioxide, or a mixture of two or more such conductive materials.

[0057] The current collector is not particularly limited as long as it does not cause chemical changes in the corresponding battery and has high conductivity. Specific examples of the current collector may include stainless steel, copper, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium or silver, etc.

[0058] The binder resin can be a polymer currently used in the art for electrodes. Non-limiting examples of binder resins include, but are not limited to: poly(vinylidene fluoride-co-hexafluoropropylene), poly(vinylidene fluoride-co-trichloroethylene), polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, poly(ethylene-co-vinyl acetate), polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan and carboxymethyl cellulose.

[0059] The electrode assembly prepared as described above may be introduced into a suitable case and an electrolyte may be injected therein to obtain a battery.

[0060] According to the present invention, the electrolyte is A + B - A salt of the structure + Including alkali metal cations such as Li + 、Na + , K + or a combination thereof, B - Including anions such as PF 6 - , BF 4 - , Cl - Br - ,I - , ClO 4 - , AsF 6 - , CH 3 CO 2 - CF 3SO 3 - 、N(CF 3 SO 2 ) 2 - , C(CF 2 SO 2 ) 3 - Or a combination thereof, the salt is dissolved or dissociated in an organic solvent selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma-butyrolactone (g-butyrolactone), ester compounds, and mixtures thereof. However, the present disclosure is not limited thereto.

[0061] In addition, the present disclosure provides a battery module, which includes a battery including the electrode assembly as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source. Specific examples of the device include, but are not limited to: an electric tool driven by the power of an electric motor; an electric vehicle, including an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), etc.; an electric two-wheeled vehicle, including an electric bicycle and an electric scooter; an electric golf cart; a power storage system; etc.

[0062] The following will be described more completely in order to easily understand the present disclosure. However, the following embodiments may be embodied in many different forms and should not be construed as being limited to the exemplary embodiments set forth herein. On the contrary, these exemplary embodiments are provided to make the present disclosure thorough and complete and to fully convey the scope of the present disclosure to those skilled in the art.

[0063] Example 1

[0064] (1) Preparation of insulating porous layer components

[0065] PVdF (Tm 164°C, Tg -40°C, Mw 1,400,000 g / mol) was dissolved in NMP to prepare a polymer solution having a solid content of 5 wt%. 5040nm) is introduced into NMP and dispersed therein using a ball mill to prepare a dispersion (solid content 50 weight %). Ball milling is carried out for 3 hours with a bead size of 0.5cm. Then, a homodiper is used to mix the polymer solution with the dispersion to prepare a composition for an insulating porous layer. The mixing is carried out for about 30 minutes at a rate of about 2000rpm. Based on the total weight of 100% of the binder resin and the inorganic particles, the content of the binder resin in the insulating porous layer is about 20%. The resulting composition is applied to a glass plate to a thickness of 350μm using a rod coater device.

[0066] The glass plate coated with the composition was introduced into a convection oven and dried at 150° C. for 30 minutes, and then the glass plate was removed to obtain an insulating porous layer member. The obtained insulating porous layer member was cut into a size of 8 cm×10 cm (width×length).

[0067] (2) Stretching of insulating porous layer components and preparation of insulating porous layers

[0068] Then, the insulating porous layer component was stretched under heating. One end of the insulating porous layer component was clamped by a first clamp fixed to the top of the oven, and the other end of the insulating porous layer component was clamped by a second clamp weighing about 466 g, and then a tensile force was applied in the direction of gravity. The stretching was performed in a convection oven at 160° C. for about 10 minutes. In this way, the insulating porous layer component was stretched to obtain an insulating porous layer. Two insulating porous layer samples were prepared in the same manner, one of which was designated as Example 1-1 and the other was designated as Example 1-2.

[0069] Example 2

[0070] An insulating porous layer sample was prepared in the same manner as in Example 1, except that PVdF (Tm 160° C., Tg −40° C., Mw 1,400,000 g / mol) was used.

[0071] Example 3

[0072] An insulating porous layer sample was prepared in the same manner as in Example 1, except that PVdF (Tm 150° C., Tg −40° C., Mw 600,000 g / mol) was used.

[0073] Comparative Example 1

[0074] An insulating porous layer was prepared by performing only the stretching step of item (1) in Example 1 without performing the stretching step of item (2) in Example 1. Two insulating porous layer samples were prepared in the same manner, one of which was designated as Comparative Example 1-1 and the other as Comparative Example 1-2.

[0075] Comparative Example 2

[0076] An insulating porous layer was produced by performing only the stretching step of item (1) in Example 2 without performing the stretching step of item (2).

[0077] Comparative Example 3

[0078] An insulating porous layer was produced by performing only the stretching step of item (1) in Example 3 without performing the stretching step of item (2).

[0079] Calculation of elongation

[0080] The elongation rate refers to the ratio (%) of the increase in the length of the diaphragm after elongation based on the initial length of the diaphragm, and can be expressed by the following formula.

[0081] Elongation (%)={(length of the membrane extended after stretching−initial length of the membrane) / initial length of the membrane}×100.

[0082] Determination of crystallinity

[0083] The crystallinity was measured using a nuclear magnetic resonance (NMR) spectrometer (Agilent 600NMR, equipped with a 1.6 mm magic angle spinning (MAS) probe) under the test conditions of a single pulse experiment, wherein d1=30 s, ns varied from 64 to 1744, and the MAS frequency was 35 kHz. According to the following Table 1, Examples 1 and 2 showed a crystallinity of more than 50%, while Comparative Examples 1 and 2 showed a low crystallinity of less than 50%.

[0084] Determination of tensile strength

[0085] Each insulating porous layer of the embodiment and the comparative example is cut into a size of 15mm x 150mm to prepare a sample. Each insulating porous layer sample is attached to a slide glass in such a way that it can correspond to the minor axis direction and the major axis direction of the slide glass. One end of the insulating porous layer located on the slide glass and the other end of the insulating porous layer not attached to the slide glass are mounted on a universal testing machine (UTM), and then the two ends are stretched in opposite directions to measure the breaking strength. Here, the UTM is operated at a rate of 500mm / min, and the length of the measuring unit is 100mm. The results are shown in Table 1 below.

[0086] Determination of dimensional changes

[0087] Each insulating porous layer of the embodiment and the comparative example was cut into a size of 15 cm x 15 cm to prepare a sample. Ethylene carbonate / ethyl methyl carbonate / dimethyl carbonate were mixed at a volume ratio of 3:3:4, and 1.0 M LiPF was added thereto. 6As a lithium salt to prepare an electrolyte. Each insulating porous layer sample was impregnated with 10 mL of electrolyte for 1 hour, and then the width and length changes of each insulating porous layer were measured to calculate the dimensional change. The results are shown as average values. Referring to Tables 1 and 2, Comparative Example 1 shows a 1.8-fold increase in length compared to Example 1, and Comparative Example 2 shows an increase in length of about 1.5 times compared to Example 2.

[0088] Determination of resistance

[0089] The resistance of each insulating porous layer sample of the embodiment and the comparative example was measured as follows. 6 Dissolved in a mixed solvent containing ethylene carbonate, propylene carbonate and propyl propionate in a volume ratio of 25:10:65 to a concentration of 1 M to prepare an electrolyte. Each insulating porous layer sample was impregnated with the electrolyte, and the resistance was measured using a multi-probe analyzer (Hioki Co.). As can be seen from Table 1 below, the insulating porous layer sample of the embodiment showed lower resistance than the insulating porous layer sample of the comparative example.

[0090] [Table 1]

[0091] Example 1-1 Example 1-2 Example 2 Example 3 Elongation(%) 8 2 8 8 Thickness(μm) 15.2 15.3 15.5 15.3 Gurley air permeability (seconds / 100cc) 119 326 150 165 Resistance(Ω) 0.55 0.92 0.62 0.69 Crystallinity(%) 60 62 58 54 <![CDATA[Tensile strength (Kgf / cm 2 )]]> 147 165 162 135 Dimensional change (%) 1.0 1.0 1.2 1.1

[0092] [Table 2]

[0093] Comparative Example 1-1 Comparative Example 1-2 Comparative Example 2 Comparative Example 3 Elongation(%) - - - - Thickness(μm) 15.7 14.4 16.2 15.8 Gurley air permeability (seconds / 100cc) 162 333 192 200 Resistance(Ω) 0.55 0.95 0.75 0.83 Crystallinity(%) 39 46 52 48 <![CDATA[Tensile strength (Kgf / cm 2 )]]> 121 164 140 110 Dimensional change (%) 1.8 1.5 2.0 2.0

Claims

1. A method for manufacturing a self-supporting separator for an electrochemical device, wherein the self-supporting separator comprises only an insulating porous layer, the method comprising: 1) preparing a composition for forming an insulating porous layer comprising inorganic particles and a binder resin, 2) applying the composition to a release sheet, drying and removing the release sheet to obtain an insulating porous layer, and 3) the insulating porous layer is stretched in at least one direction at an elongation of 10% or less, The insulating porous layer comprises inorganic particles and a binder resin, wherein the inorganic particles are present in an amount of 70 to 90 wt % based on 100 wt % of the insulating porous layer; the binder resin comprises a polyvinylidene fluoride homopolymer in an amount of 50 wt % or more based on 100 wt % of the binder resin, and the crystallinity of the binder resin is 50% or more; wherein, in the insulating porous layer, the inorganic particles are bonded to each other by the binder resin so that they are stacked in a layered structure, and the insulating porous layer has a porous property of pores originating from interstitial volumes between the inorganic particles; Wherein, elongation = {(length of the insulating porous layer after stretching - initial length of the insulating porous layer) / initial length of the insulating porous layer} x 100; The step of stretching the insulating porous layer is performed under heating and is performed within a temperature range from a glass transition temperature of the binder resin to a melting point of the binder resin.

2. The method of claim 1, wherein: The inorganic particles include at least one selected from the group consisting of Al2O3, AlOOH, Al(OH)3, AlN, BN, MgO, Mg(OH)2, SiO2, ZnO, TiO2 and BaTiO3.

3. The method of claim 1, wherein: The average particle size of the inorganic particles is 0.001 μm to 3 μm.

4. The method of claim 1, wherein: The molecular weight (Mw) of the polyvinylidene fluoride homopolymer is 600000 g / mol to 2000000 g / mol.

5. The method of claim 1, wherein: The insulating porous layer has a rectangular planar shape with a width-to-length ratio greater than 1, and the method includes the step of stretching the insulating porous layer in a transverse direction and / or a longitudinal direction.

Citation Information

Patent Citations

  • Vaporization device systems and methods

    KR1020190130072A

  • porous layer

    CN106848160B

  • Porous separating film and electrochemical device containing the same

    KR1020190049604A

  • A battery separator, its method of production and anon-aqueous secondary battery

    WO1998059384A1

  • Freestanding, heat resistant microporous film for use in energy storage devices

    WO2010108148A1